2014
DOI: 10.1016/j.ijmm.2014.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes induced in Vibrio cholerae in a dynamic biofilm system

Abstract: The facultative human pathogen Vibrio cholerae, the causative agent of the severe secretory diarrheal disease cholera, persists in its aquatic reservoirs in biofilms during interepidemic periods. Biofilm is a likely form in which clinically relevant V. cholerae is taken up by humans, providing an infective dose. Thus, a better understanding of biofilm formation of V. cholerae is relevant for the ecology and epidemiology of cholera as well as a target to control the disease. Most previous studies have investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 83 publications
5
35
0
Order By: Relevance
“…As stated above, the biofilm formed in the late logarithmic phase showed the highest amount of eDNA that might allow efficient attachment of bacterial cells to surfaces and among themselves to develop a healthy biofilm. Similar to this finding, several workers also reported the presence of eDNA in the biofilm matrix of many bacteria, B. cereus, P. aeruginosa, S. epidermidis, E. faecalis including V. cholerae (O'Gara, 2007;Thomas et al, 2008;Tang et al, 2013;Seper et al, 2014;Panda and Singh, 2018). eDNA acts as an essential element in the initiation of biofilm formation and the maintenance of biofilm.…”
Section: Detection Of Edna In Biofilmsupporting
confidence: 73%
See 2 more Smart Citations
“…As stated above, the biofilm formed in the late logarithmic phase showed the highest amount of eDNA that might allow efficient attachment of bacterial cells to surfaces and among themselves to develop a healthy biofilm. Similar to this finding, several workers also reported the presence of eDNA in the biofilm matrix of many bacteria, B. cereus, P. aeruginosa, S. epidermidis, E. faecalis including V. cholerae (O'Gara, 2007;Thomas et al, 2008;Tang et al, 2013;Seper et al, 2014;Panda and Singh, 2018). eDNA acts as an essential element in the initiation of biofilm formation and the maintenance of biofilm.…”
Section: Detection Of Edna In Biofilmsupporting
confidence: 73%
“…Both nucleases are induced at the late stage of mature biofilm, where nucleases are involved in the detachment process triggering biofilm dissolution. After that, utilizing degraded eDNA as a source of phosphate under nutrient limitation (Seper et al, 2014). In contrast, eDNA is secreted independent of cell lysis in the early stage of biofilm.…”
Section: Detection Of Edna In the Supernatant Of Batch Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we recently adapted RIVET to identify genes induced during biofilm formation of V. cholerae, representing its aquatic lifestyle. 40 Amongst other interesting candidates, extracellular nucleases were found to be induced during biofilm formation, which resulted in the characterization of extracellular DNA as a novel matrix component of V. cholerae biofilms. 41 Similarly, identification of Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Flagella involved in swimming and swarming play a role during the adhesion initial phase of biofilm formation, whereas type IV pili participate in the biofilm maturation [74]. Flagella and pili are often present in Vibrio cells [75,76]. Raguenes et al [40] have shown that V. diabolicus cells display one single flagellum in liquid medium and many lateral pili on a solid medium, which can contribute to swarming.…”
Section: Diabolicusmentioning
confidence: 99%